Zuzanna Ginczanka: krytyka, poezja, życie. O tym, jak otwierają się znaki - Zając, Marta (Iudaica Russica, 2020)
The article is an attempt to grasp a feature of the literary and cultural phenomenon of Zuzanna Ginczanka, a Ukrainian-born Polish poetess of the Jewish origin. It refers to 1) biographical elements, 2) their mediation in chosen critical works, as well as 3) the samples of Ginczanka’s literary output. The key concept for my investigations is openness (understood mainly as indeterminacy of meaning), which I associate with the intellectual climate of postmodernism, to trace, however, the modalities and variations of openness in Ginczanka’s life, criticism and poetry.